Upaya Hukum Praperadilan dalam Sistem Peradilan Pidana di Indonesia - I Made Wisnu Wijaya Kusuma; I Made sepud; Ni Made Sukaryati Karma (Jurnal Interpretasi Hukum, 2020)
Criminal justice system and Indonesian criminal procedural law adhere to presumption of innocence.So, a person must protect his human rights. KUHAP formed a new institution, namely pretrial. Based on this research authors raise formulation problems: 1. How pretrial regulation criminal justice system Indonesia, 2. How validity pretrial that has not been decided if the subject matter case has been tried. Type research used normative. approach method used statutory approach, shortening analysis legal concepts. pre-trial authority according to Article 77 Criminal Procedure Code examines whether or not coercive measures are arrest and detention well examine whether or not termination investigation or prosecution, compensation and rehabilitation legal or not. Judge Sarpin stated that Sprindik, which became the basis for Budi Gunawan's investigation, was invalid. pretrial regulations are regulated Law No. 8 of 1981 on Criminal Procedure Law in article 77 Criminal Procedure Code, namely pretrial, which authority district court examine and decide, Constitutional Court Number 21/PUU -XII/2014, authority pre-trial institution also includes whether or not determination suspects valid, searches and confiscation. Validity investigations carried out by KPK regarding determination suspect Budi Gunawan was invalid therefore determination had no binding legal force. The Subject matter pretrial case being tried declared null and void.